MAN 4 Aceh Besar في تدريس الاستماع بـــ Fun Easy Learn Arabic استخدام برنامج - Ulfa, Rizqia; Mahmud, Salami (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2024)
From observations conducted by the researcher at MAN 4 Aceh Besar, it was revealed that Arabic language teachers only use textbooks and PowerPoint presentations, apply selective teaching methods, and strive to teach Arabic well. However, students feel bored and uninterested in learning Arabic, especially in listening lessons, which makes it difficult for them to understand the material being taught. The researcher found that students have difficulty in remembering vocabulary, perhaps due to the lack of suitable teaching methods for teaching listening skills. Therefore, the researcher aims to develop students' abilities in learning Arabic, especially in listening lessons. Thus, the researcher wrote this thesis entitled "The Use of Fun Easy Learn Arabic Application in Teaching Listening". The aim of this research is to determine the effectiveness of using the Fun Easy Learn Arabic Application in teaching listening. In this study, the researcher used an experimental research method, known as the One Group Pre-test Post-test Design. The tools used to collect data were a test list, namely pre-test and post-test. Data analysis used the Wilcoxon Sign Rank Test, which showed a significance level Sig. (2-tailed) of 0.00, lower than the significance level of 0.05, indicating that the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected.